PENGARUH PERBANDINGAN NANAS (Ananas comosus L. Merr.) DAN SAWI HIJAU (Brassica juncea L.) TERHADAP KARAKTERISTIK SELAI - Azhari Saputro, Tito; Mayun Permana, I Dewa Gede; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
The aim of this research was to know effect the ratio of pineapple and mustard greens to the characteristic of jam, and determine the best ratio made by those, to produce a good characteristic of jam. This research used Complete Random Design with the treatment comparison of pineapple and mustard green comprised of 5 (five) treatments, such as 100% pineapple : 0% mustard greens, 95% pineapple : 5% mustard greens, 90% pineapple : 10% mustard greens, 85% pineapple : 15% mustard greens, 80% pineapple : 20% mustard greens. All of treatments were repeated for 3 times to obtain 15 research units. Data were analyzed using analysis of variance and if an influences occurred among the treatments, the research would be continued to the Duncan’s test. Results of this research had showed that the comparison ratio of pineapple and mustard greens gave influences to the water content, total sugar, total calcium, total soluble solid, viscosity, pH balance, texture, color, flavour, taste and overall acceptance of a jam. The best ratio of pineapple and mustard greens showed of percentage 90% pineapple : 10% mustard greens with characteristics : 25,58% water content, 57,45% total sugar, 6.176 mg/100g calcium, 59,15%brix total soluble solids, viscosity 64580 cps, 4,65 pH, texture (very like), color (like), flavor (like), taste (very like) and overall acceptance (very like).